Power balance modes and dynamic grid power flow in solar PV and battery storage experimental DC-link microgrid - Dhar, Rupak Kanti (2021)
In this paper, an energy management system, based on different power balance modes and dynamic grid power flow, is proposed to operate a DC-link microgrid based on a solar photovoltaic generator and battery storage, with the option to request variable power from the grid to meet the load demand. The energy management provides the required references, for each mode, based on the solar source availability, the battery status, the power losses, and the grid billing rate. A fuzzy logic system is developed to provide a dynamic grid power flow based on the grid price. Eight power balance modes are defined based on the power generation, storage, and grid affordability to meet the load demand. The objectives are to minimize the energy cost and increase the lifespan of the storage device. The microgrid is controlled to maintain a constant DC-link voltage and regulate the battery current depending on the mode of operation. The proposed energy management system, based on the power balance modes, is experimentally validated on a laboratory-scale DC-link microgrid for different conditions. The experimental results have shown the satisfactory performance of the microgrid and smooth transitions between the different power balance modes.